Riddick : Rule the Dark - Twohy, David; Diesel, Vin.; Karl Urban (Universal)
Left for dead on a sun-scorched planet, Riddick finds himself up against an alien race of predators. Activating an emergency beacon alerts two ships: one carrying a new breed of mercenary, the other captained by a man from Riddick's past.
David Twohy.
Language(s) : English, Espanol, Francais. Subtitle(s) : English, Espanol, Francais.
Keywords: Action; Sci-Fi; Thriller